PERKIRAAN DAMPAK LOKASI ALTERNATIF RENCANA PELABUHAN UTAMA TERHADAP PERFORMA EKSPOR DI JAWA BARAT - Syaukat, Muhammad
Interaction between transportation system and economy can be observed in export and its connection to seaport. Export is one of economic activities that has positive impacts to economic growth generally, in this context also known as Export Led Growth, where exporting increases sectoral productivity, quality of human resource, etc, which end to economic growth. Two of important and influential determinants to export performance is availability and accessibility to seaport. Avalability and accessibility to seaport which are signed by minimum transport cost and travel time makes the increasing of export performance are more possible to occur. Thus, it can be inferred that a good accessibility to seaport gives an impact to export performance. The development of new seaport in West Java which is included in the masterplan of development of Tanjung Priok Seaport that has been overcrowded for over years as stated in Regional Land Use Planning of West Java 2009-2029—RTRW—and in Ministry of Transportation Regulation No. 38 2012 gives a promising opportunity to the expansion of West Java exporting acitivity that has been increasing from year 2013 to 2014 (BPS, 2015). This new seaport development as should and is expected to give a positive impact to West Java export performance. Therefore, this research aims to indentify the impact forecasting of main seaport alternatives location to the export performance of West Java Province. To achieve the aim of the research, four objectives are established. They are knowing the location aspect condition and current export performance of West Java based on Tanjung Priok Seaport location, developing the model of West Java export performance prediction based on Tanjung Priok Seaport location, knowing the location aspect condition based on Tajung Priok and new seaport location, and comparing the results of export performance prediction based on every seaport location. The methodologies used in this research are descriptive statistic analysis, spatial analysis, linear regression analysis, and quantitative descriptive analysis. According to the results of the analysis, it has been known that the regions/cities which are geographically close to the seaport location have a lower travel time and travel cost to the seaport compared to others. The variable that has the most significant and the strongest correlation to the export performance is Regional GDP at constant 2010 prices. In addition, travel time and travel cost are two variables that have a strong negative correlation to the export performance. The more minimum travel time and travel cost to the seaport is, the higher export performance can be produced. Above all, this new seaport location generally will increase the export performance of West Java. Cirebon Seaport location will give the highest positive impact to the increasing of export volume and value up to 29,2604% and 22,3702% respectively. Those increasings are followed by the decreasing of total average of travel time and travel cost up to 14,0708% and 30,1730% respectively.